2022
DOI: 10.1002/agj2.21053
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia, nitrous oxide and methane emissions from excreta of cattle receiving rumen undegradable protein

Abstract: We hypothesized that supplementation with rumen undegradable protein (RUP) during the rearing phase mitigates nitrous oxide (N 2 O), methane (CH 4 ), and ammonia (NH 3 ) emissions from excreta of Nellore animals in Urochloa brizantha 'Xaraés' pasture. The treatments applied to soil were urine and dung of animals supplemented without RUP or with RUP in the middle and end of the rearing phase. We assessed N 2 O and CH 4 emissions using a static closed chamber and NH 3 emissions using the semi-open static chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…While in the urine, N volatilization was significantly higher, with an average of 15% (Table 6). The range of N excreta lost as NH 3 in the present study was in the range of 2-21% observed in previous studies in the tropical region [10,12,30]. However, they were lower than the IPCC default emission factor of 21% from the national guidelines for greenhouse gas emissions [1,8].…”
Section: Ammonia Volatilizationsupporting
confidence: 43%
See 4 more Smart Citations
“…While in the urine, N volatilization was significantly higher, with an average of 15% (Table 6). The range of N excreta lost as NH 3 in the present study was in the range of 2-21% observed in previous studies in the tropical region [10,12,30]. However, they were lower than the IPCC default emission factor of 21% from the national guidelines for greenhouse gas emissions [1,8].…”
Section: Ammonia Volatilizationsupporting
confidence: 43%
“…Nitrification is a microbial process that oxidizes ammonia (NH 3 ) to nitrate, while denitrification is an anaerobic process that reduces nitrate to gaseous dinitrogen (N 2 ) [9,10]. Butterbach-Bahl et al [11] stated that N 2 O produced from the nitrification process can be used in denitrification or diffused in the next soil layer before being released into the atmosphere, which may decrease the N 2 O emissions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations